A comparison of neuroprotective efficacy of two novel reactivators of acetylcholinesterase called K920 and K923 with the oxime K203 and trimedoxime in tabun-poisoned rats - Kassa, Jiri; Misik, Jan; Hatlapatkova, Jana; Zdarova Karasova, Jana (Toxicology mechanisms and methods, 2017)
The ability of two newly developed bispyridinium oximes (K920, K923) to reduce tabun-induced acute neurotoxic signs and symptoms was compared with the oxime K203 and trimedoxime using a functional observational battery (FOB). The neuroprotective effects of the oximes studied combined with atropine on rats poisoned with tabun at a sublethal dose (130 μg/kg i.m.; 80% of LD50 value) were evaluated. Tabun-induced neurotoxicity was monitored by FOB at 2 h after tabun administration. The results indicate that all tested oximes combined with atropine enable tabun-poisoned rats to survive till the end of experiment while one non-treated tabun-poisoned rat died within 2 h. Both newly developed oximes (K920, K923) combined with atropine were able to markedly decrease tabun-induced neurotoxicity in the case of sublethal poisoning although they did not eliminate all tabun-induced acute neurotoxic signs and symptoms. Their ability to decrease tabun-induced acute neurotoxicity did not prevail the neuroprotective efficacy of trimedoxime and the oxime K203. Therefore, the newly developed oximes are not suitable for the replacement of currently available oximes (especially trimedoxime) in the treatment of acute tabun poisonings.
Keywords: Animals; K923; neurotoxické syndromy; Rats, Wistar; Neurotoxicity Syndromes; functional observational battery; oximy; Pyridinium Compounds; Molecular Structure; pyridinové sloučeniny; K920; trimedoxim; molekulární struktura; Oximes; Male; Trimedoxime; Neuroprotective Agents; neurotoxicity; organofosfáty; reaktivátory cholinesterasy; Tabun; rats; mužské pohlaví; zvířata; Organophosphates; Cholinesterase Reactivators; potkani Wistar; neuroprotektivní látky